Analysis of Factors Influencing User Retention on the Community Feature of The Asian Parent Application - Ningrum, Almayanti Susilia; Pamikatsih, Mae Niken; Fernanda, Rois Ali; Dwijayanti, Irmma (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2025)
The community feature in parenting apps like The Asian Parent plays a crucial role in building digital social interactions among users, especially parents. Active community engagement is a crucial factor in maintaining user retention. This study aims to analyze the factors influencing user experience retention in the community feature within The Asian Parent app using the User Experience Questionnaire (UEQ) approach. The research method involved distributing questionnaires to active app users, covering six user experience dimensions: attractiveness, clarity, efficiency, accuracy, stimulation, and novelty. The collected data were analyzed descriptively to determine the tendency of user perceptions towards each dimension. The analysis results show that hedonic dimensions, especially stimulation and novelty, have the greatest influence on user retention, followed by pragmatic aspects such as efficiency and clarity. These findings suggest that emotional experience and cognitive satisfaction play a significant role in encouraging users to remain active in the app community. This research is expected to provide insights for app developers to design more engaging, adaptive, and sustainable community features to increase user loyalty.